Detection of Salmonella spp. and diarrheagenic Escherichia coli in fresh pork sausages - Paola Bianca Barbosa Cavalin (Semina: Ciências Agrárias, 2018)
The presence of pathogenic microorganisms in meat products may result in foodborne diseases and economic losses to their producers. Small industries in the region of Londrina, Paraná, produce sausages that are commercialized in free fairs, small markets, bars, and restaurants in the city. Although these industries are inspected by the Municipal Inspection Service of Londrina, there are no data about the pathogenic microorganisms present in these products. The objective of this study was to investigate the presence of Salmonella spp. in sausages produced and sold in the region of Londrina, Paraná, and identify eae, bfp, stx1, stx2, hlyA, ipaH, elt, est, aggR, aap, and AA probe genes in Escherichia coli strains isolated from these samples. Forty-six samples of three types of sausages (fresh pork, Tuscan, and Calabresa) produced by four different producers (brands A, B, C, and D) were analyzed. Salmonella spp. was isolated from 13 (28.3%) and E. coli from 33 (71.3%) of the analyzed samples. Seven (53.8%) of 13 samples contaminated with Salmonella spp. were from brand A. Salmonella spp. contamination was the highest in the Tuscan sausage samples (8/17, 41.7%) when compared with the fresh pork sausage samples of all brands analyzed. E. coli was isolated from 12 of 13 samples contaminated with Salmonella spp. One sample of Calabresa sausage was contaminated with atypical enteropathogenic E. coli serotype O108:H9 that has the eae and hlyA genes. The results suggest contamination of the processing plant and/or raw meat used in the manufacture of sausages. A better inspection of the industries is required to ensure that Good Manufacturing Practices are followed by which the contamination of products by pathogenic bacteria can be prevented.